The connection between a victimhood type of a personality and features of his/her life purport orientations (for example: internally displaced people and soldiers from the zone ATO – zone of anti-terrorist-operations) - Коваленко, А. Б.; Бондар, О. В. (Київський національний університет імені Тараса Шевченка, 2017)
The article is devoted to the research on social and psychological and individual determinants of soldiers from the ATO zone (zone of anti-terrorist-operations) and internally displaced people and average citizens’ victim behaviour. The results of empirical research show connection between a victimhood type of a personality and life-sense orientations. The internally displaced people have the highest level of victimhood. And the lowest level is in the soldiers from the ATO zone. The factors of victim behaviour have been revealed.

Стаття присвячена дослідженню віктимності та її чинників у групах військовослужбовців, вимущених переселенців та пересічного населення. Виявлено взаємозв’язок типу віктимності особистості та смисложиттєвих орієнтацій. Найвищий рівень віктимності виявлено у групі вимушених переселенців, найнижчий – у військовослужбовців. З’ясовано чинники віктимної поведінки.
Зв’язок типу віктимності особистості з особливостями її смисложиттєвих орієнтацій (на прикладі вимушених переселенців та військовослужбовців)
Keywords: victimization; life-sense orientations; meaningfulness of life; rental aim; віктимність; смисложиттєві орієнтації; осмисленість життя; рентні установки